PROBLEMS OF ENSURING THE CONTINUITY OF THE SUBJECT "COMPYUTER SCIENCE AND INFORMATION TECHNOLOGY" IN THE SYSTEM OF CONTINUING EDUCATION - Zulayho Abdullayevna Marasulova; Makhfuza Khabibovna Zakhidova (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the problems of ensuring continuity in the teaching of "computer science and information technology" in the system of continuing education.